In Vitro Study of Dentin Hypersensitivity Treated by 980-nm Diode Laser - Ying, Liu; Gao, Jie; Gao, Yan; XU, Shuaimei; Zhan, Xueling; Wu, Buling (Journal of Lasers in Medical Sciences, 2013)
Introduction: To investigate the ultrastructural changes of dentin irradiated with 980-nm diode laser under different parameters and to observe the morphological alterations of odontoblasts and pulp tissue to determine the safety parameters of 980-nm diode laser in the treatment of dentin hypersensitivity (DH). Methods: Twenty extracted human third molars were selected to prepare dentin discs. Each dentin disc was divided into four areas and was irradiated by 980-nm diode laser under different parameters: Group A: control group, 0 J/cm²; Group B: 2 W/CW (continuous mode), 166 J/cm²; Group C: 3W/CW, 250 J/cm²; and Group D: 4W/CW, 333 J/cm². Ten additional extracted human third molars were selected to prepare dentin discs. Each dentin disc was divided into two areas and was irradiated by 980-nm diode laser: Group E: control group, 0 J/cm²; and Group F: 2.0 W/CW, 166 J/cm². The morphological alterations of the dentin surfaces and odontoblasts were examined with scanning electron microscopy (SEM), and the morphological alterations of the dental pulp tissue irradiated by laser were observed with an upright microscope. Results: The study demonstrated that dentinal tubules can be entirely blocked after irradiation by 980-nm diode laser, regardless of the parameter setting. Diode laser with settings of 2.0 W and 980-nm sealed exposed dentin tubules effectively, and no significant morphological alterations of the pulp and odontoblasts were observed after irradiation. Conclusions: Irradiation with 980-nm diode laser could be effective for routine clinical treatment of DH, and 2.0W/CW (166 J/cm²) was a suitable energy parameter due to its rapid sealing of the exposed dentin tubules and its safety to the odontoblasts and pulp tissue.